2022
DOI: 10.1242/jcs.259018
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophilin A regulates the apoptosis of A549 cells by stabilizing Twist1 protein

Abstract: Cyclophilin A (CypA) is an essential member of the immunophilin family. As an intracellular target of immunosuppressive drug cyclosporin A (CsA) or a peptidyl-prolyl cis/trans isomerase (PPIase), it catalyzes the cis-trans isomerization of proline amidic peptide bonds, through which, it regulates a variety of biological processes, such as intracellular signaling, transcription, and apoptosis. In this study, we found that intracellular CypA enhanced Twist1 phosphorylation at Ser68 and inhibited apoptosis in A54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…PPIA (Cyclophilin A) is a member of the immunophilin family and acts as an immune inflammatory mediator that secretes oxidative stress-induced, which promotes the formation of foam cells by increasing the levels of ROS and pro-inflammatory cytokines. Furthermore, PPIA is involved in biological processes such as intracellular signaling, transcription, and apoptosis, therefore playing critical roles in microorganismal infections, inflammatory diseases, and tumor proliferation [32][33][34]. An increase in PPIA levels may lead to macrophage apoptosis through activation of mitochondrial death signaling pathways and caspase 3 cascade [35].…”
Section: Discussionmentioning
confidence: 99%
“…PPIA (Cyclophilin A) is a member of the immunophilin family and acts as an immune inflammatory mediator that secretes oxidative stress-induced, which promotes the formation of foam cells by increasing the levels of ROS and pro-inflammatory cytokines. Furthermore, PPIA is involved in biological processes such as intracellular signaling, transcription, and apoptosis, therefore playing critical roles in microorganismal infections, inflammatory diseases, and tumor proliferation [32][33][34]. An increase in PPIA levels may lead to macrophage apoptosis through activation of mitochondrial death signaling pathways and caspase 3 cascade [35].…”
Section: Discussionmentioning
confidence: 99%
“…In the subsequent study, we showed that OS reduced NF‐κB signaling activity to exert its anti‐RA effect, which was consistent with another report indicating the role of NF‐κB signaling in regulating RA‐FLS proliferation, migration, and invasion. 29 Furthermore, OS downregulated the expression of IL1A, IL1B, Myc, ABCG2, and vimentin, which are known NF‐κB targets, 30 , 31 as well as CCNA2, CCNB1, Twist1, and N‐ca, which are known downstream effectors of NF‐κB, 32 , 33 , 34 and caused the elevation of E‐ca expression. Moreover, ABCG2 contributed to MTX resistance in RA.…”
Section: Discussionmentioning
confidence: 99%
“…Te acccumulation of ferritin can elicit oxidative infammation and NF-κB-TNFα pathway, which may further trigger necroptosis [37]. PPIA (cyclophilin A) acts as an immune infammatory mediator that secretes proinfammatory cytokines induced by oxidative stress [38][39][40][41]. SLC25A4 encodes the adenine nucleotide translocator-1 (ANT1), which is involved in metabolism via the regulation of ATP/ADP release from mitochondria and in regulated cell death as part of the mitochondrial permeability transition pore [42].…”
Section: Discussionmentioning
confidence: 99%